Análise da condução de calor transiente uni e bidimensional submetidas as harmônicas térmicas nas condições de contorno - Silveira, Igor Cavalcanti da (2012)
The thermal properties of materials are vital to the integrity of mechanical designs, mainly of thermal systems and their components. The simulation and determination of temperature field brings the representation of the thermal behavior, i.e., provides previous information on how the temperature varies with position and time in a given solid, subject to certain conditions, characterizing thermically the material, implying what are applications most appropriate for that object under study. For the solution of partial differential equations governing heat diffusion problems in the present study, we used the generalized integral transform technique (GITT), both for the one-dimensional model as the two-dimensional with harmonic oscillating temperature as a boundary condition, providing the temperature profile of the models under study. These were simulated by a computer code developed in Mathematica 8.0, and with the results obtained, an analysis of convergence with respect to temperature observing the number of eigenvalues was done. The one-dimensional model was reproduced by two-dimensional model, assuming the Biot number equal zero of the condition of the third kind of cylinder lateral surface in twodimensional model, for validation of both; and comparing the results of de model with the experimental results.